In search of a parameter to distinguish viable from non-viable articular cartilage - Indentation and ultrasound studies - Brown, C; Crawford, R; Oloyede, A (2008)
It has been recently established that mechanical indentation does not sufficiently discriminate between normal and degraded articular cartilage. Consequently, we have carried out preliminary research to develop and evaluate a number of indices and parameters that can characterise and categorise the tissue into viable and degraded types relative to functional integrity. In this paper, we report the outcome of correlation studies between the instantaneous structural rebound following unloading from a known level of indentation and reflected ultrasound signals, analysed in the frequency domain. We subjected 137 samples from 10 normal and 10 osteoarthritic joints to ultrasound waves and mechanical indentation-rebound tests, and determined the degree of correlation between the instantaneous rebound and the principal components of the ultrasound spectra and further investigated this using canonical discriminate analysis that was fitted with a general linear model. Our results demonstrate a strong correlation between rebound and ultrasound results, leading to the conclusion that it is possible to determine the mechanical and structural viability of articular cartilage using non-contact methods.